IN-VITRO DIGESTIBILITTY OF BARLEY GRAINS TREATED WITH UREA: IN-VITRO STUDY - & et al., Tawfeeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in a central laboratory of Agriculture College\ University of Baghdad, to study the effect of treated barley grains with urea as 1: 1 urea: barley grain (w:w) with or without heating on the in-vitro digestibility, total nitrogen content and releasing urea, the results showed a high significant increases (P